The Hydrocarbon Potential of Carboniferous Reservoirs in the Jimsar Sag, Northwest China: Implications for a Giant Volcanic-Petroleum Reserves - Gong, Deyu; Song, Yong; Peng, Miao; Liu, Chaowei; Wang, Ruiju; Wu, Wei’an (Frontiers in Earth Science, 2022)
As an unconventional petroleum reservoir, the volcanic reservoir is essential for finding large-scale oil and gas reserves in deep sedimentary basins. Based on basin modeling, organic geochemistry, and organic petrology, this study evaluates the exploration potential of the Carboniferous volcanic-petroleum system in the Jimsar Sag of the southeastern Junggar Basin. The Carboniferous source rocks in the study area were developed in the Lower Carboniferous Songkharsu Formation, a set of marine–terrigenous transitional source rocks, lithologically composed of carbonaceous mudstone, mudstone, and coal. The kerogen is characterized by type II2–III, indicating a gas-prone source rock. Carbonaceous mudstones, mudstone, and coal are classified as medium–good, medium, and poor source rocks, respectively. The hydrocarbon-generating potential is close to that of the Kelameili gas field. The Carboniferous-reservoir oil in well J15 is characterized by 13C-enriched stable carbon isotopes, relatively high ƩC31–35/C30 and Pr/Ph ratios, relatively low density, gammacerane index, regular C29-sterane content, and undetected β-carotene, indicating a Songkharsu origin. The Carboniferous-reservoired gas from well J3301 has stable carbon isotope composition enriched in 13C, similar to the gas from the Kelameili gas field, and should be from the Songkharsu source rock. This set of source rocks is widely distributed in the Jimsar Sag with considerable thickness, among which thickness >100 m reaches 580 km2, accounting for 38.7% of the whole sag. The Songkharsu source rocks entered the main oil-generating window at the end of the Early Jurassic. The area of Songkharsu source rocks in the Jimsar Sag with gas-generating intensity greater than 20 × 108 m3/km2 reaches 1015 km2, whereas that with oil-generating intensity greater than 500 × 104 t/km2 reaches 1146 km2. However, 13 Carboniferous volcanic lithological traps were found in the sag, covering an area of 230 km2. The Carboniferous volcanic-petroleum system in the Jimsar Sag has the resource potential to form large and medium oil and gas fields, which could become a critical replacement field for volcanic oil and gas exploration in the Junggar Basin after the Klameili gas field.